(untitled) (Research, Society and Development, 2020)
Objective: Evaluate the fasting time and postoperative complications of patients undergoing elective surgery in a university hospital. Methodology: This was a cross-sectional study carried out on surgical patients admitted to the Hospital Universitário de Lagarto from April 2018 to April 2019. For data collection, a semi-structured form was used that included questions related to the sociodemographic profile, clinical diagnosis, screening and nutritional assessment, fasting time and postoperative complications. The individuals were allocated into two groups, according to the preoperative fasting time: group 1 ≤ 15h and group 2> 15h. Α = 5% was considered in the statistical analyzes. Results: Of the 128 patients who participated in the study, 52% were classified as eutrophic and 37% as overweight; however, as for CMB, most were classified as adequate. The average total fasting time was 25 hours, with group 1 having a preoperative fasting time of 11:41 hours, while group 2 averaged 19:41 hours. Among the most frequent complications were nausea and vomiting. There was no difference between complications and preoperative time between groups. Conclusion: Patients remained in a prolonged preoperative period with intestinal, infectious and metabolic complications such as nausea, vomiting and hyperglycemia. The same patients showed good nutritional status.